The challenges of rehabilitating patients with bruxism through the use of veneers: A literature review (Research, Society and Development, 2023)
Bruxism is known as a parafunctional disorder of the stomatognathic system that manifests in various forms, such as teeth grinding or clenching. Its etiology is unknown, but it can arise due to numerous reasons, with stress being the main triggering factor. This parafunctional activity does not have a known cure, but it has multidisciplinary therapeutic approaches that can alleviate the signs and symptoms. Sleep hygiene is one of the most commonly used and recommended approaches for patients with sleep bruxism. Additionally, relaxation exercises, acupuncture, a healthy diet, and physical exercise are other effective organic approaches to improve the condition of bruxism. The field of rehabilitation is growing day by day, and the desire for white and harmonious teeth has been awakened in patients. Composite resin veneers and ceramic laminates are restorative materials that have had a significant impact in dentistry in recent times and are used therapeutically for bruxism patients. The combination of occlusal splints with these rehabilitative materials has been a positive alternative that can provide patients with protection of dental structures, masticatory function, aesthetics, and preservation of soft tissues in the oral cavity. With this, the current narrative literature review aims to analyze the challenges related to rehabilitation with veneers in bruxist patients; assess which type of bruxism poses a greater challenge for oral rehabilitation with veneers, and analyze therapeutic approaches for bruxism, including a rehabilitative approach involving the combination of occlusal splints and dental veneers made of composite resin and ceramic laminates.